The big book of dashboards visualizing your data using real-world business scenarios - Wexler, Steve 1958-; Cotgreave, Andy 1972-; Shaffer, Jeffrey 1972- (Hoboken, New Jersey John Wiley & Sons Ltd., 2017)
"The definitive reference book with real-world solutions you won't find anywhere else

The Big Book of Dashboards presents a comprehensive reference for those tasked with building or overseeing the development of business dashboards.

Comprising dozens of examples that address different industries and departments (healthcare, transportation, finance, human resources, marketing, customer service, sports, etc.) and different platforms (print, desktop, tablet, smartphone, and conference room display) The Big Book of Dashboards is the only book that matches great dashboards with real-world business scenarios.

By organizing the book based on these scenarios and offering practical and effective visualization examples, The Big Book of Dashboards will be the trusted resource that you open when you need to build an effective business dashboard.

In addition to the scenarios there's an entire section of the book that is devoted to addressing many practical and psychological factors you will encounter in your work. It's great to have theory and evidenced-based research at your disposal, but what will you do when somebody asks you to make your dashboard 'cooler' by adding packed bubbles and donut charts?

The expert authors have a combined 30-plus years of hands-on experience helping people in hundreds of organizations build effective visualizations. They have fought many 'best practices' battles and having endured bring an uncommon empathy to help you, the reader of this book, survive and thrive in the data visualization world.

A well-designed dashboard can point out risks, opportunities, and more; but common challenges and misconceptions can make your dashboard useless at best, and misleading at worst. The Big Book of Dashboards gives you the tools, guidance, and models you need to produce great dashboards that inform, enlighten, and engage."
Includes bibliographical references (pages 423-424) and index pages (425-432).
Keywords: Management information systems; Management -- Evaluation; Organizational effectiveness -- Evaluation